The Effect of Chitosan Application against Plant Growth and Intensity of Stunting Disease on Black Pepper (Piper nigrum L.) Seedlings - Emerensiana Uge; Sri Sulandari; Sedyo Hartono; Susamto Somowiyarjo (Jurnal Perlindungan Tanaman Indonesia, 2018)
Black pepper (Piper nigrum L.) is  an important estate crops in Indonesia. Some pathogens that have been known to infect black pepper plants include fungi, nematodes and viruses. The stunting disease on black pepper plants was caused by Cucumber mosaic virus (CMV). Molecular detection using RT-PCR method showed that the samples were positively infected by CMV which were amplified by specific primers CMV 111 with bands of 111 bp in size. This virus can be carried by vegetative propagation material of plants. Many control strategies against this virus have been investigated, especially inducing plant resistance with chitosan. Chitosan is a natural biopolymer that play an important role in reducing disease incidence and severity and stimulate plant growth. The aim of this study was to figure out the inhibiting  ability of chitosan solution against infection of stunting virus on black pepper seedlings through spraying applications. Chitosan treatments were prepared in concentrations of 0.5%, 0.75%, and 1%. The result showed that application of chitosan at all concentrations affected the decrease of disease incidence and intensity and improved plant growth with insignificant different amongst all treatments but significantly different with control. The highest decrease in incidence was found at 0.75% of chitosan concentration (26.37), while the highest decrease of intensity was expressed at 1% of chitosan (37.62). Application of chitosan also significantly affected to all parameters of plant growth either plant height or leaf diameter. Application of 1% of chitosan increased the percentage of plant growth rather than other treatments, with the increase of plant height 58.12 % and leaf diameter 54.74 %. IntisariLada (Piper nigrum L.) merupakan salah satu tanaman perkebunan penting di Indonesia. Beberapa patogen telah diketahui menginfeksi tanaman lada di antaranya jamur, nematoda, dan virus. Penyakit kerdil pada tanaman lada disebabkan oleh Cucumber mosaic virus (CMV). Deteksi molekuler menggunakan metode RT-PCR menunjukkan bahwa sampel positif terinfeksi CMV yang diamplifikasi menggunakan primer spesifik CMV 111 dengan ukuran pita band target 111 bp. Virus ini dapat terbawa bahan perbanyakan tanaman secara vegetatif. Banyak strategi pengendalian virus yang telah diuji, diantaranya induksi ketahanan tanaman dengan kitosan. Kitosan adalah biopolimer alami yang berperan dalam menurunkan insidensi dan intensitas penyakit dan menstimulasi pertumbuhan tanaman. Tujuan dari penelitian ini adalah untuk mengetahui kemampuan penghambatan dari larutan kitosan terhadap infeksi dari virus kerdil pada bibit lada dengan aplikasi penyemprotan. Konsentrasi kitosan yang digunakan adalah 0,5%; 0,75%; dan 1%. Hasil penelitian menunjukan bahwa apliksi kitosan pada semua konsentrasi berpengaruh dalam menurunkan insidensi dan intensitas penyakit dan meningkatkan pertumbuhan tanaman dengan tidak berbeda nyata di antara perlakuan tetapi berbeda nyata dengan kontrol. Penurunan nilai insidensi tertinggi yakni pada aplikasi kitosan 0,75% (26,37), sedangkan penurunan nilai intensitas tertinggi yakni pada aplikasi kitosan 1% (37,62). Aplikasi kitosan juga berpengaruh signifikan terhadap semua parameter pertumbuhan tanaman baik tinggi tanaman maupun diameter daun. Pada aplikasi kitosan 1% meningkatkan persentase tinggi tanaman lebih baik dibandingkan dengan perlakuan lainnya,yakni tinggi tanaman sebesar 58,12 % dan diameter daun sebesar 54,74 %.